Physiological functionalities and mechanisms of β-glucans. (June 2019) - Bai, Junying; Ren, Yikai; Li, Yan; Fan, Mingcong; Qian, Haifeng; Wang, Li; Wu, Gangcheng; Zhang, Hui; Qi, Xiguang; Xu, Meijuan; Rao, Zhiming
Abstract: Background: β -Glucans are polysaccharides constructed of glucose monomers linked by β -glucosidic bonds, which mainly exist in cereals (barley and oat), yeast and mushrooms. Some physiological functionalities of β -glucans have been confirmed, consequently, their development and utilization in the biomedical, pharmaceutical, food, and cosmetic industries have received increasing interest. Foods and dietary supplements containing β -glucans are very popular. Scope and approach: This review summarizesrecent findings regarding thephysiological functionalities of β -glucans and details theaction mechanisms of β -glucans upon the present knowledge. The prospects for future research on these topics are also discussed. Key findings and conclusions: β -Glucans are effective in many aspects of human health, including cancer prevention, reducing glycemia and serum cholesterol, anti-inflammation, as well as improving immunity. The modification of β -glucans contributes to better solubility, viscosity and gelation, which can change the bioactivities of β -glucans. The action mechanisms of β -glucans and their derivatives are considered to be mainly mediated by somecytokines and hormones in subjects. Human health is supported by various mechanism researches. Although certain action mechanisms remain unclear, the clarification of how β-glucans exhibit biological effects is beneficial for our understanding of complicated biochemical reaction in living organisms. Highlights: The origins, extraction, characteristics and modification of β -glucans were reviewed. The physiological functionalities and mechanisms of β -glucans were presented. Possible links among different bioactive mechanisms of β -glucans were detailed. β -glucans' enormous development potentials and prospects were discussed.